Early Murnau: Five Films, 1921-1925 [Medienkombination] - Israel, Robert; Brand, Neil; Becce, Giuseppe (Eureka Video, 2016)
One of the most influential and revered figures in all of cinema, Friedrich Wilheim Murnau came to prominence in the first half of the 1920s with a diverse string of productions ranging from buoyant satire to swirling psychological drama. Five key works are presented here: Schloß Vogelöd, Phantom, Die Finanzen des Großherzogs (The Grand Duke’s Finances), Der Letzte Mann (The Last Laugh) and Tartuffe. This collection features new high-definition transfers of all five films from the finest archival elements, all on Blu-ray for the first time in a special edition three-disc set. [www.eurekavideo.co.uk]
Keywords: Blu-Ray-Disc